Accuracy Synthesis of a 2UPS & UPR & UP Parallel Robot - Zhu Chao; Sun Zaichao; Zhang Jun (Jixie chuandong)
An accuracy synthesis approach for a 2UPS & UPR & UP parallel robot is proposed. Based on the nominal kinematic equations, an error mapping model of the robot is established using the perturbation method, and the compensable and uncompensable geometric error sources are sorted out. The standard deviation relationship between the uncompensable error sources and the terminal attitude errors is established to reveal the standard deviation distribution of the terminal attitude error in the workspace. A sensitivity analysis of the uncompensable error sources is carried out to determine the influence of each uncompensable geometric error source on the terminal accuracy. According to the 3σ principle, the sensitivity index is taken as the allocation coefficient, and the values of the uncompensable error sources under the given terminal accuracy are obtained through the accuracy synthesis. The proposed approach can provide a theoretical basis for the manufacturing of the robot, and the effectiveness of the proposed method is verified by simulation.